2015
DOI: 10.1007/s11164-015-2182-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and photoluminescence properties of difluoroboron complexes with bis-β-diketone ligands

Abstract: Some novel difluoroboron bis-b-diketonates containing a pyridyl moiety were synthesized from diethyl 2,6-pyridinedicarboxylate via Claisen condensation with the corresponding aryl methyl ketones and followed by complexation with boron trifluoride etherate. Their spectroscopic behaviors were studied by FTIR, 1 H NMR, UV-Vis, and fluorescence spectroscopic techniques. The results indicated that difluoroboron bis-b-diketonates exhibited violet or blue fluorescence emission at 428-454 nm under UV illumination in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Remember that fluorophores containing dioxaborinine core have been widely reported; [5–12,26,32–34] nevertheless, those bearing the pyrazolo[1,5‐ a ]pyrimidine ring are rare, although some interesting examples have been reported in our research group [16,17,22,29,35,36] . Fluorophores of extended π‐conjugation ( Py‐DB , R 2 ‐DB , and TPA‐DB 3 ) and with various substitutions such as phenyl ( Ph 2 ‐DB ), methoxyaryl ( Py‐DB , R 2 ‐DB , and Ar‐PP ), TPA ( TPA‐DB , TPA‐DB 3 , and TPA‐PP ), and coumarin ( Cum‐DB ) groups were used in this analysis.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Remember that fluorophores containing dioxaborinine core have been widely reported; [5–12,26,32–34] nevertheless, those bearing the pyrazolo[1,5‐ a ]pyrimidine ring are rare, although some interesting examples have been reported in our research group [16,17,22,29,35,36] . Fluorophores of extended π‐conjugation ( Py‐DB , R 2 ‐DB , and TPA‐DB 3 ) and with various substitutions such as phenyl ( Ph 2 ‐DB ), methoxyaryl ( Py‐DB , R 2 ‐DB , and Ar‐PP ), TPA ( TPA‐DB , TPA‐DB 3 , and TPA‐PP ), and coumarin ( Cum‐DB ) groups were used in this analysis.…”
Section: Resultsmentioning
confidence: 96%
“…498/532 98500 1300 65 DCM [À À ], Suhasini et al [30] 430/527 -4300 49 DMF [À À ], Haucke et al [34] 366/397 40700 2100 39 Toluene [20], Yang et al [32] 379/468 18000 5000 77 CyH [3], Tigreros et al [35] 502/570 129000 2400 61 DCM [1], Chaicham et al [33] 353/479 5100 7500 44 DCM [10], Castillo et al [36] 449/531 87100 3300 85 CHCl 3 [10], Tigreros et al [12] 347/477 17700 7900 69 THF [20], This work 386/454 40700 3900 93 DMSO [20], Wang et al [26] [a] If no information is reported by the authors in the respective work, we assume that such dyes are obtained starting from commercial substrates. distribution throughout the molecule due to the high πconjugation in this compound (Figure 2a).…”
Section: Computational Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The bis-b-diketone, 3,3 0 -pyridin-2,6-diyl-bis(1-phenylpropane-1,3-dione), was prepared by Claisen condensation of diethyl 2,6-pyridinedicarboxylate with acetophenone in toluene using sodium as condensing agent according to literature [16].…”
Section: Synthesis Of 26-bis(5-phenyl-1h-pyrazol-3-yl)pyridine (Bpp)mentioning
confidence: 99%